Internalization of Character Education Values Through Civic Education Learning in the Digital Era: Strategies and Multidimensional Collaboration - Yuni Nuryanti Putri Hidayah; I Nengah Suastika; Dewa Bagus Sanjaya (FKIP - Universitas Riau, 2026)
This study aims to describe the process of internalizing character education values through Civic Education learning in the digital era, focusing on strategies and multidimensional collaboration in the school environment. The background of this research lies in the growing challenges of moral degradation and the decline of students’ social awareness due to excessive digital exposure. Using a descriptive qualitative method, the study collected data through interviews, observations, and documentation in a junior high school context. The findings indicate that teachers play a central role in integrating character values by combining digital learning platforms with contextual moral instruction. The use of digital media such as interactive videos, online discussions, and collaborative projects enhances students’ participation and strengthens their understanding of civic and ethical responsibilities. However, the study also found obstacles such as limited digital literacy among teachers and the inconsistent implementation of value-based learning. It is concluded that effective internalization of character education in the digital era requires synergy between teachers, parents, and the educational community supported by strong digital competence and moral guidance.